(untitled) (Research, Society and Development, 2022)
Objective: To identify in the scientific literature the ways in which nurses work with high-risk pregnant women. Methodology: Systematic literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method, performed in the electronic databases BDENF, Lilacs, Pubmed and Web of Science, using the following descriptors: “High-risk pregnancy”, “Care of nursing” and “Obstetrical nursing”. Full articles were included, available in Portuguese, English or Spanish, published between January 2016 and October 2021. Results: 11 articles comprised the final sample of this study. Regarding the role of nurses in high-risk pregnancy, from the sample of articles, it was possible to list the following thematic axes: 1. Implementation of the Nursing Care Systematization (SAE) in the therapeutic plan for pregnant women at risk; 2. Use precepts recommended by the Ministry of Health in order to guarantee humanized care - reception: emotional and informational support; 3. Carry out the assessment and monitoring of gestational risk and carry out technical-scientific care in the treatment of diseases associated with gestational risk and during childbirth and puerperium; 4. Conduct health education constantly in high-risk pregnant women. Conclusion: It was found that care for high-risk pregnant women was evident through quality prenatal care, based on the individualized care plan organized by the nurse, under the support of the family and through the use of Systematization of Care of Nursing, of light technologies and by the process of health education.